Assessment of Female Reproductive Endpoints in Sprague-Dawley Rats Developmentally Exposed to Diuron: Potential Ovary Toxicity - Grassi, Tony Fernando [UNESP]; Guerra, Marina Trevisan; Perobelli, Juliana Elaine; de Toledo, Fabiola Choqueta [UNESP]; da Silva, Denise Salioni [UNESP]; Kempinas, Wilma de Grava [UNESP]; Barbisan, Luis Fernando [UNESP] (Wiley-Blackwell, 2011)
BACKGROUND: Diuron is widely used in agriculture but its deleterious effects on the reproductive system and mammary gland are still poorly understood. This study evaluated whether early-life-stage exposure to Diuron alters puberty onset or susceptibility to mammary carcinogenesis in female Sprague-Dawley rats. METHODS and RESULTS: Pregnant rats received basal diet or diet containing Diuron at 500, 750, and 1,250 ppm, from gestational day 12 to the end of lactation (postnatal day 21 [PND21]). After weaning, female offspring continued receiving basal diet or diet containing Diuron until PND 51. At PND 51, female Sprague-Dawley offspring received a single dose of 50 mg/kg b.w. of 7,12-dimethylbenz(a) anthracene (DMBA) for initiation of mammary carcinogenesis. The animals were sacrificed on PND 51, 75, and 226 to 233 (week 25) for mammary gland morphology, reproductive organs and tumor analysis, respectively. There were no significant differences among groups on vaginal opening, estrous cycle, mammary morphology, or carcinogenesis. However, reductions in ovary weight and corpora lutea were observed at PND 75 in the group treated with Diuron at 1,250 ppm. CONCLUSIONS: The findings suggesting that Diuron exposure (1,250 ppm) may have been potentially toxic to the ovaries. Birth Defects Res (Part B) 92:478-486, 2011. (C) 2011 Wiley Periodicals, Inc.
Keywords: diuron; maternal exposure; female offspring; reproduction; mammary carcinogenesis; Sprague-Dawley rats